PENGARUH TERAPI DZIKIR TERHADAP TINGKAT KECEMASAN PADA PASIEN PRE DAN POST OPERASI - Nurlina; Nursyamsi (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2019)
Postoperative surgery and trauma are stressors that can cause physiological and psychological reactions to the patient. Psychological reactions in the form of anxiety usually arise in the preoperative stage when the patient anticipates surgery and at the postoperative stage because of pain and discomfort, changes in body image and bodily functions. Handling anxiety with spiritual aspects in the form of dzikir therapy is an effort to reduce anxiety levels in patients pre and post surgery. This study used a pre-experimental research design with a one group pre and posttest design study design. The sample of this study was 15 respondents in the experimental group taken by consecutive sampling method. The experimental group received a dzikir therapy 1 time treatment with a duration of 12 minutes. Data collection is done using a questionnaire sheet. Analysis of the data used in this study is univariate and bivariate by using a paired sample t test. The results of the analysis used a statistical test paired sample t test with a level of confidence (α = 0.05). Based on the results of this test, the p value is 0,000, thus p <α (0,000 <0,05). The conclusion of this study is that there is an effect of giving dzikir therapy to the level of anxiety in patients pre and post surgery. Researchers suggest that the results of this study can be used as a reference for application in the scope of nursing services, especially handling anxiety.